2011
DOI: 10.22488/okstate.18.100419
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink Consumption and its Effects on Student Pilots: Perceptions of Collegiate Flight Students

Abstract: During the past ten years, there have only been a few published research studies examining the possible behavioral consequences of energy drink consumption by college students. With that in mind, the authors surveyed collegiate aviation flight students regarding their consumption of energy drinks and their perceptions of side effects and behavioral patterns after consuming energy drinks. Results show that 57% of student pilots surveyed consume energy drinks 1-3 times a week. In addition, 56% stated they can on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
(8 reference statements)
0
3
1
Order By: Relevance
“…This high rate may be found because college students have hard schedules and can be under a great amount of stress. One way students think for fighting this problem is by consuming energy drinks to get that much needed boost of energy [17]. Our result is higher than Bulut, et al, 2014, who conducted a study at the Karadeniz Technical University in Turkey and found that 46.5 % of students had ever tried energy drinks [18].…”
Section: Discussioncontrasting
confidence: 53%
“…This high rate may be found because college students have hard schedules and can be under a great amount of stress. One way students think for fighting this problem is by consuming energy drinks to get that much needed boost of energy [17]. Our result is higher than Bulut, et al, 2014, who conducted a study at the Karadeniz Technical University in Turkey and found that 46.5 % of students had ever tried energy drinks [18].…”
Section: Discussioncontrasting
confidence: 53%
“…The bibliographic and scientometric data for all articles were reported in Table S2. 25 of 71 papers were published on journals which do not have the Journal Impact Factor (JIF) [35,[37][38][39]41,43,45,[52][53][54]60,61,64,67,70,[72][73][74]78,79,87,90,92,95] 18 journals have JIF between 0.219 and 1.883 while 27 have JIF between 2.333 and 7.325 and only one has a JIF above the threshold of 20 [40].…”
Section: Nr = Not Reportedmentioning
confidence: 99%
“…Frequent EDs consumers were found to have smoked cigarettes, abused drug prescriptions, and were involved in violent activities. They also engaged themselves in unsafe sex, doing extreme sports, and dangerous stunts [6]. The study also showed that the consumption of EDs leads to other bad and dangerous habits of consuming other stronger stimulants and drugs which may destroy the career of people especially pilots.…”
Section: B Health Issuesmentioning
confidence: 92%
“…The reason behind that is that the Arab countries do not consider drinking EDs as a health problem. In fact, it has not reached the alarming levels of being called a problem [6]. Another issue is that there are a small number of people who have reached the level of addiction, and we do not have reported cases that directly link the harm caused as a result of over consuming EDs.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation